A COMPARATIVE STUDY OF SENSORY ATTRIBUTES AND EFFICACY BETWEEN INTRANASAL CICLESONIDE AND FLUTICASONE PROPIONATE IN ALLERGIC RHINITIS - MADHU YASARAPU; AMMAR KHALID; SHUBHAM JAJU; SAMAR MAHMOOD (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study was to compare the clinical efficacy, sensory tolerability, and overall patient preference between fluticasone propionate (FLP) and ciclesonide (CIC) in patients with allergic rhinitis (AR). Methods: An observational, crossover study was conducted at a tertiary ENT hospital in Hyderabad from December 2020 to November 2022. A total of 120 adult patients (n=120, 60 per sequence) with moderate-to-severe AR (total nasal symptom score [TNSS] ≥6) were enrolled. Participants received a single intranasal dose of FLP 200 mcg or CIC in a randomized sequence with a 30‑min washout period before crossover. TNSS scores were recorded at baseline and 10 min post‑dose. Sensory attributes were evaluated using a validated 7‑point Likert scale, and overall treatment preference was recorded after both sprays. Data were analyzed using the Statistical Package for the Social Sciences v26, with p<0.05 considered significant. Results: Both sprays produced a significant reduction in TNSS within 10 min (median reduction: 5 points in both groups, p<0.001). Between‑group comparison showed no significant difference in total TNSS change (p=0.774). Ocular itching improved significantly with FLP compared to CIC (19.2% vs. 12.5%, p=0.0442), while other nasal symptoms (sneezing, congestion, nasal itch, and rhinorrhea) showed no significant differences. Sensory evaluation revealed that FLP was preferred for soothing feel (58.3% vs. 22.5%, p<0.0001) and satisfying scent (55% vs. 8.3%, p<0.001), whereas aftertaste and throat sensations were slightly better with CIC. Overall, 59.4% of patients preferred FLP, 28.3% CIC, and 12.3% had no preference. Conclusion: FLP and CIC are both effective and well‑tolerated for AR management. Fluticasone showed marginally superior ocular symptom relief and higher patient preference, while CIC offered slightly better throat tolerability. Tailoring intranasal corticosteroid selection to patient‑reported sensory experience may enhance adherence and clinical outcomes.